Facilitating equitable access to hospice care in socially deprived areas: A mixed methods multiple case study - Maddy French; Thomas Keegan; Nancy Preston (SAGE Journals, 2022)
Background:
There is uncertainty about the factors influencing inequities in access to palliative care in socially deprived areas, including the role of service models and professional perceptions.
Aim:
To explore the relationship between social deprivation and access to hospice care, including factors influencing access and professional experiences of providing care.
Design:
A mixed-methods multiple case study approach was used. Hospice referrals data were analysed using generalised linear mixed models and other regression analyses. Qualitative interviews with healthcare professionals were analysed using thematic analysis. Findings from different areas (cases) were compared in a cross-case analysis.
Setting:
The study took place in North West England, using data from three hospices (8699 hospice patients) and interviews with 42 healthcare professionals.
Results:
Social deprivation was not statistically significantly, or consistently, associated with hospice referrals in the three cases (Case 1, Incidence Rate Ratio 1.04, p = 0.75; Case 2, Incidence Rate Ratio 1.09, p = 0.15, Case 3, Incidence Rate Ratio 0.88, p = 0.35). Hospice data and interviews suggest the model of hospice care, including working relationship with hospitals, and the local nature of social deprivation influenced access. Circumstances associated with social deprivation can conflict with professional expectations within palliative care.
Conclusion:
Hospice care in the UK can be organised in ways that facilitate referrals of patients from socially deprived areas, although uncertainty about what constitutes need limits conclusions about equity. Grounding professional narratives around expectations, responsibility, and choice in frameworks that recognise the sociostructural influences on end-of-life circumstances may help to foster more equitable palliative care.
Keywords: 110308 Geriatrics and Gerontology; 111702 Aged Health Care